2016
DOI: 10.1007/s12094-016-1523-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HER2 expression on outcome in gastric cancer patients with liver metastasis

Abstract: HER2 positivity was higher in GCLM patients. HER2 status itself was not an independent prognostic factor in GCLM patients. Trastuzumab-based therapy could significantly improve survival in HER2-positive GCLM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Retrospective studies have shown that T1–3 disease, H1, R0 resection followed by systemic chemotherapy were important prognostic factors for gastric cancer patients with liver metastasis [150, 151]. In addition, it has been found that the HER2 gene amplification rate in gastric cancer patients with liver metastasis was higher and that these patients would be more likely to gain a survival benefit from anti-HER2 targeted therapy [152]. Krukenberg tumors are the metastatic lesion of gastric cancer that have been metastasized to the ovary (one or both).…”
Section: Comprehensive Treatment Of Gastric Cancermentioning
confidence: 99%
“…Retrospective studies have shown that T1–3 disease, H1, R0 resection followed by systemic chemotherapy were important prognostic factors for gastric cancer patients with liver metastasis [150, 151]. In addition, it has been found that the HER2 gene amplification rate in gastric cancer patients with liver metastasis was higher and that these patients would be more likely to gain a survival benefit from anti-HER2 targeted therapy [152]. Krukenberg tumors are the metastatic lesion of gastric cancer that have been metastasized to the ovary (one or both).…”
Section: Comprehensive Treatment Of Gastric Cancermentioning
confidence: 99%
“…Furthermore, HER2 overexpression was significantly higher in GEJC as compared to other locations [ 26 ], and it has a high correlation with the presence of the intestinal histological type [ 27 ]. Since the intestinal type has been associated with hematogenous metastasis [ 28 ], this might be an explaining link to the positive correlation between HER2 overexpression and hepatic metastases [ 28 , 29 ]. Additionally, several studies have found a high concordance rate of HER2 expression between primary and secondary sites, which suggests that generally HER2 status remains stable during the metastatic process [ 9 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors even speculate that GC liver metastases are a unique clinical entity sharing the same characteristics [ 31 ], like sensitivity to HER2-targeting drugs. Hence, Tmab could reverse the poor outcome of HER2-positive GC in these young patients, particularly with liver metastases [ 29 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The specific mechanisms underlying the CTCs expressing HER2 and promoting tumor cells survival in the blood circulation have not yet been fully elucidated. Supposedly, the expression of HER2 in CTCs could promote cell survival and proliferation through the PI3K/Akt and Ras/Raf/MAPK signaling pathway [ 10 , 11 ]. Banys-Paluchowski et al detected CTCs and serum HER2 (sHER2) levels using the CellSearch system and ELISA, respectively.…”
Section: Biology Of Ctcsmentioning
confidence: 99%